2017
DOI: 10.1186/s12971-017-0149-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between employer’s knowledge and attitude towards smoking cessation and voluntary promotion in workplace: a survey study

Abstract: BackgroundWorkplace smoking cessation (SC) intervention is effective in increasing quit rate but little was known about the factors associated with voluntary SC promotion. Comprehensive smoke-free legislation, including banning smoking in all indoor area of workplaces, has been enforced in Hong Kong. This survey investigated the prevalence of company’s compliance with smoke-free legislation and examined the relation between voluntary SC promotion in workplace and employer’s knowledge of and attitude towards sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Company‐level workplace support might help to increase motivation to quit smoking [32]. We have previously reported that some companies (15%) were not compliant with the smoke‐free workplace ordinance in Hong Kong [9]. Among the few (10.0%) companies that had ever promoted smoking cessation voluntarily in workplaces, most employers only adopted simple and passive strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Company‐level workplace support might help to increase motivation to quit smoking [32]. We have previously reported that some companies (15%) were not compliant with the smoke‐free workplace ordinance in Hong Kong [9]. Among the few (10.0%) companies that had ever promoted smoking cessation voluntarily in workplaces, most employers only adopted simple and passive strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The SCPW project was organized by the Lok Sin Tong Benevolent Society Kowloon (LST), which is the only service provider for smokers in workplaces in Hong Kong. Details of this project have been reported elsewhere [9, 10]. The present study protocol was approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster (UW12–550) and registered with ClinicalTrials.gov (NCT03142555).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More training for employees may enhance their knowledge towards smoking hazards and improve employees' support for tobacco control in the workplace [34], thereby promoting the implementation of smoke-free policy in the workplace. The most immediate authority at the workplace is the employers [35]. Employers support the "Qingdao Tobacco Control Regulation" in the workplace and are more inclined to devise plans to increase knowledge and attitude towards tobacco control of the employees through training program or an awareness campaign [10], reducing their exposure to second-hand smoke in the workplace, thereby reducing employees' cotinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that persons with more knowledge of the effects of tobacco on health are associated with greater likelihood of tobacco cessation (Chow et al, 2017; Yang, Hammond, Driezen, Fong, & Jiang, 2010). Another study reported that employers with a higher level of knowledge of smoking are more likely to promote smoking cessation in the workplace (Wang et al, 2017), while pregnant women who have less knowledge about passive smoking are significantly more likely to be exposed to SHS (Norsa’adah & Salinah, 2014; Yang, Tong, Mao, & Hu, 2010). Considering these results, knowledge about smoking and passive smoking could be an important factor in improving people’s health outcomes, especially during pregnancy.…”
Section: Introductionmentioning
confidence: 99%